377 دور الذكاء الاصطناعي التوليدي في تعزيز مجالات التنمية المستدامة : The Role of Generative Artificial Intelligence in Promoting Sustainable Development - حسن ربيع ماجد خشبة ، بسمة الحداد وأخرون (معهد التخطيط القومي, 2026)
يستعرض البحث دور الذكاء الاصطناعي التوليدي في دعم التنمية المستدامة بأبعادها الاقتصادية والاجتماعية والبيئية. ويؤكد على الفرص الكبيرة التي تتيحها هذه التقنيات في تحسين جودة الحياة وتعزيز الابتكار عالميًا. كما يناقش التحديات المرتبطة بالخصوصية وحقوق الملكية الفكرية والتحيزات والمسؤوليات القانونية. ويتناول تطور الذكاء الاصطناعي وتحليل الأبحاث العالمية باستخدام أدوات تحليلية متقدمة. ويقدم إطارًا استشرافيًا لحوكمة الذكاء الاصطناعي التوليدي لضمان استخدامه بشكل مسؤول ومستدام. The study explores how generative artificial intelligence reshapes sustainable development across economic, social, and environmental dimensions. It highlights its potential to improve quality of life, foster innovation, and create jobs worldwide. It also addresses key challenges such as privacy, intellectual property, algorithmic bias, and legal accountability. The research reviews global developments and analytical studies on generative AI using advanced research methods. It proposes a forward-looking governance framework to ensure responsible and effective use of generative AI for sustainability.